Gaps between fruit and vegetable production, demand, and recommended consumption at global and national levels: an integrated modelling study - Mason-D'Croz, Daniel; Bogard, Jessica R.; Sulser, Timothy B.; Cenacchi, Nicola; Dunston, Shahnila; Herrero, Mario; Wiebe, Keith D. (Elsevier, 2019)
Current diets are detrimental to both human and planetary health and shifting towards more balanced, predominantly plant-based diets is seen as crucial to improving both. Low fruit and vegetable consumption is itself a major nutritional problem. We aim to better quantify the gap between future fruit and vegetable supply and recommended consumption levels by exploring the interactions between supply and demand in more than 150 countries from 1961 to 2050.